GREEKS AND THEIR GODS - Guthrie, W. K. C. (William Keith Chambers), 1906-1981. Link ([S.l.])
1 online resource
Keywords: The Greeks and their Gods (1950) examines the question of what the Greeks thought to be the proper relationship between human and divine. Religion was such an integral part of Ancient Greek life and thought that without a proper study their world can be scarcely appreciated.